Fenomena Laki-Laki Penenun Ulos di Kecamatan Tarutung Kabupaten Tapanuli Utara - Ratih Baiduri; Rimma Natasari Sitanggang (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
In general, weaving Ulos in the Toba Etnich social culture is women’s work. What is interesting is that it turns out that there are men who are also involved in weaving activities. This research aims to explore how male ulos weavers became a phenomenon in the social and cultural life of the Toba Batak ethnic group. This research uses qualitative methods with an ethnographic motivated and driven by fulfilling life’s needs, the identity of men as ulos weavers over a long period oh time gradually began to receive a positive view from the community, however, there were still people who viewed the presence of men pessimistically. Ulos weavers from the perspective of Toba Batak cultuter.